AB1345 CONTEXTUAL FACTORS IMPACTING OSTEOARTHRITIS MANAGEMENT IN URBAN AND RURAL COMMUNITY-DWELLING SENIORS: AN ANALYSIS BASED ON THE INTERNATIONAL CLASSIFICATION OF FUNCTIONING DISABILITY AND HEALTH. (June 2019) - MacDermid, Joy; Lee, Karen; Ali, Amanda
Abstract : Background: Living with arthritis requires lifelong management that can be influenced by person, place and context. Objectives: The objectives of this study were to: (1) identify contextual factors that influence OA management in rural and urban-dwelling seniors, and (2) examine how contextual factors identified by rural and urban-dwelling seniors are explained in terms of the ICF framework Methods: Semi-structured interviews were conducted with 20 community-dwelling seniors in Ontario, Canada.; purposivel inclding 11 seniors from an urban setting and 9 seniors from a rural setting, all over the age of 65, and previously diagnosed with OA. Broad questions on self-management and information weeking were explored. Interview concepts related to the environmental and contextual factors component were extracted from interview transcripts and organized into subthemes. Meaningful concepts were linked by 2 raters to ICF categories according to established linking rules. Descriptive analyses were performed. Results: A total of 891 meaningful concepts were identified; 481 from interviews with 11 urban-dwelling seniors and were linked to 54 ICF categories: 24 Environmental Factors, 21 Activities and Participation, and 9 Body Functions and 410 meaningful concepts from interviews with 9 rural-dwelling seniors: 57 ICF categories: 27 Environmental Factors, 24 Activities and Participation, and 6 Body Functions. Within Activities and Participation component, "d839 Education" was the most code for both groups. From the Body Functions component, "b1800 Experiences of Self" followed by "b1301 Motivation" were most mentioned. Environmental factors represented 203 of 481 (42.2%) urban concepts and 253 of 410 (61.7%) rural concepts. The concepts linked to the Activities and Participation category were similar across urban and rural groups (17.3% and 17.1%). Personal Factors (e.g. "adapting to life with OA", "self-sufficiency", "pain tolerance", "age") or "nc - not covered" (e.g. "feeling old", "embarrassed by OA", "being a burden") were not coded. In 12.2% urban and 20.6% rural content was labeled as Personal Factors. Chapter e5 services, systems and policies was the chapter with the highest coverage overall. Within the environmental factors "e355 Health Professionals" was the most common code for both urban and rural groups, and mentioned in almost all interviews. Participants frequently discussed physician's attitudes and misconceptions towards patients with OA. Conclusion: The complex interaction of personal and environmental factors impacting OA management in both urban and rural communities was illustrated. Rurality influences some aspects of ths complexity, but many common themes occur. References: [1] Weigl M, Cieza A, Harder M, et al. Linking osteoarthritis-specific health-status measures to the international classification of functioning, disability, and health (ICF). Osteoarthr Cartil. 2003;11(7):519-523. doi:S1063458403000864 [pii]. [2] Cieza A, Geyh S, Chatterji S, Kostanjsek N, Üstün B, Stucki G. ICF linking rules: An update based on lessons learned. J Rehabil Med. 2005;37(4):212-218. doi:10.1080/16501970510040263. Disclosure of Interests: None declared